First molecular analysis of rabies virus in Qatar and clinical cases imported into Qatar, a case report. (July 2020) - Oude Munnink, Bas B.; Farag, Elmoubashar Abu Baker Abd; GeurtsvanKessel, Corine; Schapendonk, Claudia; van der Linden, Anne; Kohl, Robert; Arron, Georgina; Ziglam, Hisham; Goravey, Wael Goravey Mhjoop; Coyle, Peter V.; Ibrahim, Imad; Mohran, Khaled A.; et al.
Highlights: We demonstrate the presence of rabies virus in Qatar In Qatar, many street dogs and cats are susceptible to rabies virus Migrant workers in remote settings are mainly at risk of acquiring rabies virus infection We showed that two human rabies virus cases were imported from Nepal to Qatar Abstract: Identifying the origin of the rabies virus (RABV) infection may have significant implications for control measures. Here, we identified the source of a RABV infection of two Nepalese migrants in Qatar by comparing their RABV genomes with RABV genomes isolated from the brains of a RABV infected camel and fox from Qatar.